Comparison of therapeutic efficacy of different drugs against Trypanosoma vivax on experimentally infected cattle - Bastos, Thiago Souza Azeredo (2020)
In this study, we evaluated the therapeutic efficacy of diminazene diaceturate at a dose of 7 mg/kg (DA), imidocarb dipropionate at 4.8 mg/kg (IMD), isometamidium chloride at 0.5 and 1.0 mg/kg (ISM 0.5 and ISM 1.0) and combinations applied through different methods to treat Trypanosoma vivax in experimentally infected calves. Thirty male Girolando calves were kept indoors and infected intravenously with T. vivax trypomastigotes (approximately 1 × 106). On D-1, the calves were randomized based on the quantity of infecting parasites per animal, yielding six groups of five animals each: G1: positive control group without treatment; G2 animals treated with DA on Day 0 intramuscularly (IM); G3 animals treated with IMD on Day 0 and D + 14 subcutaneously; G4 animals treated with ISM 0.5 on Day 0 IM; G5 animals treated with ISM 1.0 on Day 0 IM; G6 animals received DA on Day 0 and ISM 1.0 on D + 14, both IM. Throughout 180 days, blood samples were collected for the evaluation of T. vivax using the Woo, Brener and PCR methods. The results indicated that the treatment protocols with DA and/or ISM 0.5 and ISM 1.0 had high efficacy (100 %) against T. vivax. Interestingly, cattle that received ISM remained free of parasites until D + 180. In contrast, animals treated with IMD had relapsed T. vivax detected on the 10th and 14th days post-treatment (DPT). Cattle that received ISM 1.0 did not exhibit relapsed T. vivax in the blood, even after reinfection performed on the 50th DPT. However, treatment with DA on Day 0 failed to prevent a new infection of T. vivax on the 50th DPT. The animals that received ISM 1.0 had a transient decrease in packed cell volume similar to that found in the control group. The reappearance of T. vivax in herds in Brazil treated with DA likely occurred due to the short half-life of the drug and not necessarily due to T. vivax resistance to DA.